2017
DOI: 10.1002/pssa.201700216
|View full text |Cite
|
Sign up to set email alerts
|

Proximity gettering technology for advanced CMOS image sensors using carbon cluster ion‐implantation technique: A review

Abstract: A new technique is described for manufacturing advanced silicon wafers with the highest capability yet reported for gettering transition metallic, oxygen, and hydrogen impurities in CMOS image sensor fabrication processes. Carbon and hydrogen elements are localized in the projection range of the silicon wafer by implantation of ion clusters from a hydrocarbon molecular gas source. Furthermore, these wafers can getter oxygen impurities out‐diffused to device active regions from a Czochralski grown silicon wafer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
81
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(85 citation statements)
references
References 38 publications
1
81
0
1
Order By: Relevance
“…This indicates that the novel silicon wafer has a high gettering capability for metallic impurities. (26,30) 3.2 Oxygen out-diffusion barrier effect during device heat treatment Figure 5 shows the SIMS depth profiles of oxygen impurities measured on the epitaxial silicon wafers with and without hydrocarbon molecular ion implantation after device heat treatment. The oxygen impurities out-diffused to the silicon epitaxial layer from the CZ-silicon grown substrate during the device heat treatment.…”
Section: Sample Preparation and Evaluation Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the novel silicon wafer has a high gettering capability for metallic impurities. (26,30) 3.2 Oxygen out-diffusion barrier effect during device heat treatment Figure 5 shows the SIMS depth profiles of oxygen impurities measured on the epitaxial silicon wafers with and without hydrocarbon molecular ion implantation after device heat treatment. The oxygen impurities out-diffused to the silicon epitaxial layer from the CZ-silicon grown substrate during the device heat treatment.…”
Section: Sample Preparation and Evaluation Techniquesmentioning
confidence: 99%
“…(29) This phenomenon will have a passivation effect on process-induced defects such as those in the Si/SiO 2 interface states. (30) In this review article, the main objective is to demonstrate the metal, oxygen, and hydrogen impurity gettering capability of the hydrocarbon-molecular-ion-implanted silicon wafer using the CMOS image sensor fabrication process. Furthermore, we investigate the effect of white spot defects on the CMOS image sensor with and without hydrocarbon molecular ion implantation for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has been reported that hydrocarbon ion implantation into Si crystals using hydrocarbon molecules with large molecular weight results in less damage to the Si crystals than ion implantation of molecules with low molecular weight . As amorphous carbon films are used more and more in combination with Si crystals in electronic devices and the like, reducing damage to the Si crystals is important.…”
Section: Introductionmentioning
confidence: 99%
“…В последние годы [1][2][3][4][5][6] имплантация ионов различных химических элементов широко используется на практике для разработки и производства микроэлектронных полупроводниковых приборов. Особый интерес представляет использование в качестве инструмента радиационного легирования кристаллических подложек ионов Н + (протонов).…”
Section: Introductionunclassified